Escalations in the East China Sea: Is Conciliation Possible? - Tan, Ming Hui (2016)
Responding to both domestic and external pressures, China sends a strong signal by raising tensions in the East China Sea. Japan is likely to continue engagement of Southeast Asia to balance the perceived Chinese provocation. Can China and Japan explore conciliatory options to avoid a worsening security situation in the region?